A dynamic network model of the unsecured interbank lending market - Francisco Blasques; Falk Bräuning; Iman van Lelyveld (Federal Reserve Bank of Boston, 2016)
We introduce a dynamic network model of interbank lending and estimate the parameters by indirect inference using network statistics of the Dutch interbank market from mid-February 2008 through April 2011. We find that credit-risk uncertainty and peer monitoring are significant factors in explaining the market's sparse core-periphery structure and the presence of relationship lending. Shocks to credit-risk uncertainty lead to extended periods of low market activity, intensified by a reduction in peer monitoring. Moreover, changes in the central bank's interest-rate corridor have a direct effect on the market as well as an indirect effect that acts to change banks' monitoring efforts.
Keywords: C33; C51; E52; G01; G21; 330; interbank liquidity; financial networks; credit-risk uncertainty; peer monitoring; monetary policy; trading relationships; indirect parameter estimation